Immanuel in our place seeing Christ in Israel's worship - Longman, Tremper, III, 1952- (Phillipsburg, NJ Presbyterian and Reformed, 2001)
Includes bibliographical references and index.
Keywords: Public worship in the Bible; Bible. O.T. -- criticism, interpretation, etc; Bible. O.T. -- relation to the New Testament; Bible. N.T. -- relation to the Old Testament